2010
DOI: 10.1016/j.commatsci.2010.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of discontinuous dynamic recrystallization in pure Cu using a probabilistic cellular automaton

Abstract: A cellular automaton algorithm with probabilistic cell switches is employed in the simulation of dynamic discontinuous recrystallization. Recrystallization kinetics are formulated on a microlevel where, once nucleated, new grains grow under the driving pressure available from the competing processes of stored energy minimization and boundary energy reduction. Simulations of the microstructural changes in pure Cu under hot compression are performed where the influence of different thermal conditions are studied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
69
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 113 publications
(71 citation statements)
references
References 48 publications
(86 reference statements)
0
69
0
2
Order By: Relevance
“…The reason for such a difference may be because that the elongated grain boundaries provide more potential nucleation sites for recrystallization due to a higher ratio of the grain boundary volume to grain volume. At the same time, the newly formed recrystallized grains impinge earlier with support of the morphology change of the matrix, resulting in a smaller average grain size as compared to the conventional CA simulation [5][6][7][8][9][10][11][12][13][14][15][16][17][18]. In addition, it can be also found that the grain morphology deformation has a decreased effect on the critical strain for DRX.…”
Section: Simulation Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reason for such a difference may be because that the elongated grain boundaries provide more potential nucleation sites for recrystallization due to a higher ratio of the grain boundary volume to grain volume. At the same time, the newly formed recrystallized grains impinge earlier with support of the morphology change of the matrix, resulting in a smaller average grain size as compared to the conventional CA simulation [5][6][7][8][9][10][11][12][13][14][15][16][17][18]. In addition, it can be also found that the grain morphology deformation has a decreased effect on the critical strain for DRX.…”
Section: Simulation Results and Discussionmentioning
confidence: 99%
“…In this case, initial grain size, initial grain orientation and dislocation density are used as input data to the CA model; the flow curve, dislocation density, finial grain size and orientation and recrystallized fraction are the output data. Hallberg et al [11] employed the CA model with probabilistic cell switches in simulating DRX of pure Cu. Ding et al [12] investigated the hot compression behavior of the Mg-9Al-1Zn alloy using EBSP analysis and the CA method.…”
Section: Introductionmentioning
confidence: 99%
“…Plotting Equation (1) in a double-logarithmic diagram allows convenient identification of the parameters B and n A . The Avrami exponent n A , given by the slope of the plot, gives some indication of the character of the nucleation process, i.e., if site-saturated or continuous nucleation takes place, and changes if two-or three-dimensional results are considered [2,6,19]. Limitations and modifications of the KJMA model are discussed in [20][21][22].…”
Section: Classical Results and Empirical Modelsmentioning
confidence: 99%
“…The formulation in Equation (5) corresponds to the proportional nucleation model in [30,31]. Expressions for the nucleation rate as in Equation (5) have been used in Monte Carlo modeling of recrystallization in [35,36] and in cellular automata models in [19,37,38]. Once nucleated, the recrystallized grains can grow due to a driving pressure p acting on the grain boundary.…”
Section: Classical Results and Empirical Modelsmentioning
confidence: 99%
See 1 more Smart Citation